Are the results of clinical trials relevant in the real world? The applicability of REDUCE-IT to the FAST-MI Registry. (25th November 2020) - Ferrieres, J; Bataille, V; Puymirat, E; Schiele, F; Simon, T; Danchin, N
Abstract: Background: Large clinical trials are often criticized for testing therapeutic strategies in selected populations. The REDUCE-IT data revealed robust atherosclerotic cardiovascular risk reduction with a strategy comprising of high dose omega-3 icosapent ethyl versus placebo in statin treated patients with triglyceride values (TG) between 150 and 499 mg/dl and controlled LDL-C (41–100 mg/ dl). Purpose: In order to evaluate the applicability of REDUCE-IT in a French population, we applied the inclusion and exclusion criteria in the French Registry on Acute ST- elevation and non-ST-elevation Myocardial Infarction (FAST-MI) [2010 and 2015]. Methods: From the FAST-MI registry, we included patients over 45 years, who had detailed lipid values post-acute hospitalization [11.1 months (median) after hospitalization for myocardial infarction]. We thus compared the applicability of REDUCE-IT [in patients with TG between 150 (or 200) and 500 mg/dl and an LDL-C between 40 and 100 mg/dl while treated with statin therapy] in the FAST-MI registry focusing on the general characteristics, the risk factors, and the cardiovascular prognosis i.e. the rate of total mortality, myocardial infarction and stroke. Results: 12.5% of the patients (5.5% if TG between 200 and 500 mg/dl) met the eligibility criteria for REDUCE-IT. The differences between the REDUCE-IT like (n=472) and REDUCE-IT excluded (n=3317) samples were related to age (61 vs 65, NS), male gender (79.5% vs 73.8%, p<0.01), body mass index in kg/m 2 (28 vs 26.2, p<0.001), current smoking (45% vs 31.4%, p<0.001), hypertension (56.5% vs 50.2%, p<0.01), and the percentage of diabetic patients (29.5% vs 15.6%, p<0.001). In the REDUCE-IT like sample, the mean values of total cholesterol, TG (median) and the HDL-C were respectively 159, 192, 43 and the LDL-C value was 72 mg/dl. The distribution of the statin regimens in the REDUCE-IT like sample was as follows: 65.3%, 32.4% and 2.3% had high, moderate and low intensity statin therapy. The distribution of TG categories in the REDUCE-IT like sample was as follows: 55.3% (150–199), 36.0% (200–299) and 8.7% (300–500 mg/dl). The subgroup with TGs greater than 200 mg/dl and HDL-C less than 35 mg/dl was 16.1% in the REDUCE-IT like group and 2.1% in the REDUCE-IT excluded group (p<0.001). The cardiovascular event rate (death, nonfatal MI, nonfatal stroke) was respectively 36.7 for the FAST-MI REDUCE-IT like group and 36.9 persons-years (CVD death, nonfatal MI, nonfatal stroke) for the REDUCE-IT trial. Conclusion: The cardiovascular residual risk related to elevated TG in the applicable patient population in the FAST-MI registry was similar to the risk in REDUCE-IT. If the results of REDUCE-IT are applied to patients hospitalized for a myocardial infarction in France, on top of statins, 12.5% of these patients could benefit from a strategy of high dose omega-3 icosapent ethyl on top of contemporary medical therapy to improve their future cardiovascular health. Funding Acknowledgement: Type of funding source: None